Risk and protective factors for incidents of intimate partner violence among active-duty military personnel - Valerie A. Stander; Travis N. Ray; Sabrina M. Richardson; Kelly A. Woodall; Cynthia J. Thomsen; Joel S. Milner; James E. McCarroll; David S. Riggs; Stephen J. Cozza (PLoS ONE, 2026)
Purpose Intimate partner violence (IPV) among military personnel harms service members and their partners and has implications for military readiness. Understanding modifiable risk and protective factors for IPV perpetration in this context is important for prevention and response. Method Data from the Millennium Cohort Study (2011–2013) were used as a baseline in a hypothesized prospective path model predicting IPV perpetration. IPV outcomes were operationalized as reports to the Department of Defense Family Advocacy Program Central Registry that occurred after baseline and met Department of Defense criteria for psychological or physical domestic abuse. Results A posttraumatic stress symptom cluster indicative of general negative affect and alcohol dependence mediated the effects of other posttraumatic stress symptoms—as well as the effects of protective factors (i.e., socioeconomic, psychosocial, physical health)—on risk of IPV perpetration. Only socioeconomic status had indirect, direct, and moderated effects on IPV perpetration. Conclusions Findings suggest future program development and evaluation should consider whether common protective factors—such as economic stability, better health (e.g., sleep quantity and quality), career satisfaction, and psychosocial factors (e.g., social support)—can be modified through integrated prevention to reduce risk for multiple interrelated outcomes (e.g., posttraumatic stress disorder, substance dependence, and IPV).